Pengaruh Karakteristik CEO terhadap Manajemen Laba pada Sektor Perbankan di Indonesia - Adimudra, Adya Puspita; Setiawan, Doddy (Universitas Prasetiya Mulya, 2025)
This study was conducted to empirically prove the influence of CEO characteristics on profit management with a sample of 269 banking observations listed on the Indonesia Stock Exchange in 2015-2021. The results of this study show that the financial education background and gender of CEOs are able to significantly improve banking profit management. The CEO's education level is able to reduce profit management practices insignificantly, while the CEO's tenure does not significantly improve banking profit management practices in Indonesia. This research only focuses on the banking sector listed on the IDX and the research period is relatively short. The implication of research on the banking sector is that knowing the character and educational background of CEOs is important.